2003
DOI: 10.1007/s00125-002-1030-3
|View full text |Cite
|
Sign up to set email alerts
|

AICA-riboside induces apoptosis of pancreatic beta cells through stimulation of AMP-activated protein kinase

Abstract: Aims/hypothesis. Prolonged exposure of beta cells to low glucose concentrations triggers their apoptosis and is known to activate AMP-activated protein kinase (AMPK) in beta cell lines. We examined whether prolonged activation of AMPK can trigger apoptosis in rodent beta cells. Methods. Primary beta cells were FACS-purified from rats, and from wild-type and AMPK(alpha2)-deficient mice. AMPK activation in beta cells was induced by the adenosine analog AICA-riboside and detected by immunoblotting using a phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 11 publications
6
81
0
2
Order By: Relevance
“…AMPK mediates a prosurvival signal initiated by adiponectin treatment of cardiomyocytes after ischemia and reperfusion and is similarly protective against neuronal apoptosis (38,39). Conversely, sustained AMPK activation by high concentrations of an AMP analog caused apoptosis of normal and cancerous B cells and can similarly impact other cell types (40,41). These opposite outcomes were due either to cell type-specific differences or the degree of AMPK activation, its duration, and cross-talk in which AMPK inhibits signaling via mTOR or exercises ACC-independent functions (42).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK mediates a prosurvival signal initiated by adiponectin treatment of cardiomyocytes after ischemia and reperfusion and is similarly protective against neuronal apoptosis (38,39). Conversely, sustained AMPK activation by high concentrations of an AMP analog caused apoptosis of normal and cancerous B cells and can similarly impact other cell types (40,41). These opposite outcomes were due either to cell type-specific differences or the degree of AMPK activation, its duration, and cross-talk in which AMPK inhibits signaling via mTOR or exercises ACC-independent functions (42).…”
Section: Discussionmentioning
confidence: 99%
“…These V-shaped glucose concentration response curves for changes in islet c-Myc and HO1 expression with a minimum at G10 are similar to that of beta cell death [29]. Whereas the stimulation of beta cell apoptosis by prolonged culture in low glucose may be due to activation of AMP-dependent protein kinase and stimulation of c-Myc expression under these conditions [23,30], it has been suggested that the deleterious effects of supraphysiological glucose concentrations on the beta cell phenotype result from NFκB activation by oxidative stress [12,[31][32][33][34] or by induction of production and autocrine actions of IL-1β [35].…”
Section: Introductionmentioning
confidence: 91%
“…Thus, AMPK promotes catabolism to enhance ATP synthesis and reduces anabolism to spare ATP utilization. Although these actions of AMPK support cell survival [8][9][10][11][12][13], activation of AMPK also has been reported to promote apoptotic cell death [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%